VERBS OF VERTICAL MOVEMENT AS A PRAGMATIC RESOURCE: A COGNITIVE-TYPOLOGICAL ANALYSIS IN ENGLISH, RUSSIAN AND UZBEK LANGUAGES - Khamraeva Malikakhon Gayrat kizi (International Journal of Literature and Language Studies, 2026)
This article examines the pragmatic potential of causative verbs of vertical movement (поднять, опустить, ko'tarmoq, tushirmoq, raise, lower, and their derivatives) in three typologically distinct languages: Russian (fusional), Uzbek (agglutinative), and English (analytic). Drawing upon conceptual metaphor theory and the classification of spatial metaphors developed for the Russian verbal lexicon, the study demonstrates how vertical verbs serve not only to describe physical displacement but also to express social, moral, and emotional evaluations, regulate interpersonal distance, and implement politeness strategies. The comparative material reveals that, despite the universality of the UP–DOWN spatial schema, specific lexical units and their pragmatic connotations depend on the grammatical structure and cultural priorities of each language. The article provides extensive examples from dictionary entries, corpus data, and natural speech contexts.